2000
DOI: 10.1023/a:1009082409702
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Anger attacks have been described as sudden spells of anger accompanied by symptoms of autonomic activation and have been experienced by patients as uncharacteristic of them and inappropriate to the situations in which they had occurred. The aim of this study was to assess the prevalence of anger attacks in a non-Western depressed population. We also wanted to see whether depression in patients with anger attacks was qualitatively different from depression without anger attacks. The Anger Attacks Questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
1
0
2
Order By: Relevance
“…Previous studies have revealed that patients with anger attacks are significantly more depressed, anxious and have ideas of hopelessness compared to patients without anger attacks and they were more likely to meet criteria for cluster B (histrionic, narcissistic, borderline and antisocial) personality disorders in comparison to depressed patients without anger attacks. [89] This case highlights the efficacy of CBT as a maintenance treatment for depressive illness with expressed anger, without any significant side-effect. Patient had improvement in anger outburst, mood and overall social functioning, where pharmacotherapy alone failed to show a response.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have revealed that patients with anger attacks are significantly more depressed, anxious and have ideas of hopelessness compared to patients without anger attacks and they were more likely to meet criteria for cluster B (histrionic, narcissistic, borderline and antisocial) personality disorders in comparison to depressed patients without anger attacks. [89] This case highlights the efficacy of CBT as a maintenance treatment for depressive illness with expressed anger, without any significant side-effect. Patient had improvement in anger outburst, mood and overall social functioning, where pharmacotherapy alone failed to show a response.…”
Section: Discussionmentioning
confidence: 93%
“…Раздражительность как диагностический критерий депрессии, проблема коморбидности АГ с другими психическими и поведенческими расстройствами Надежная оценка клинической ситуации как коморбидности АГ с тем или иным психическим расстройством (например, при их сочетании с РЛ или БАР), а не как одного из симптомов клини ческих проявлений текущего психического рас стройства, нередко является трудно разрешимой задачей. Большинство исследований, посвящен ных АГ, было проведено на выборках пациентов с большим депрессивным расстройством (БДР) [19,24,25,29,47,56], в результате чего оказалось, что раздражительное настроение и АГ во время де прессии не являются уникальной особенностью для детей и подростков, а является довольно рас пространенным явлением среди взрослых, стра дающих БДР. З. Фрейд в своей работе «Печаль и меланхолия» (1917) указывал на тесную связь раз дражительности, агрессии с депрессией, отмечая, что депрессивная реакция является результатом сложной трансформации агрессии, связанной с потерей значимого объекта, невозможностью вы разить агрессию из-за страха наказания [6].…”
Section: научные обзорыunclassified
“…В большинстве исследований указывается на более тяжелые клинико-динамические характе ристики в случае депрессивных расстройств с АГ (более ранний возраст к началу депрессивного расстройства, более выраженная депрессия, тре вога и чувство безнадежности, большая длитель ность депрессивного эпизода, более хроническое и тяжелое долгосрочное течение депрессивного расстройства, более высокие показатели коморбидности в течение жизни со злоупотреблением психоактивными веществами, тревожными рас стройствами и с асоциальным РЛ, более серьез ные психосоциальные нарушения), чем при «чи стых» депрессивных расстройствах [23,33,56].…”
Section: научные обзорыunclassified